Exosome-like nanoparticles: a new type of nanocarrier - Fernandes, Mário (2020)
Nanoparticles are one of the most used systems for imaging or therapeutic drug delivery. Exosomes are nanovesicular carriers that transport cargo for intercellular communication. These nanovesicles are linked to the pathology of some major diseases, in some cases with a central role in their progression. The use of these carriers to transport therapeutic drugs is a recent and promising approach to treat diseases such as cancer and Alzheimer disease. The physiological production of these structures is limited impairing its collection and subsequent purification. These drawbacks inspired the search for mimetic alternatives. The collection of exosome-like nanoparticles from plants can be a good alternative, since they are easier to extract and do not have the drawbacks of those produced in animal cells. Both natural and synthetic exosome-like nanoparticles, produced from serial extrusion of cells or by bottom up synthesis, are currently some of the most promising, biocompatible, high efficiency systems for drug delivery.